Determination of Audit Delays in Financial Sector Companies from 2021 to 2023 - Irene Gracelia Trivena; Anita Permatasari (Universitas Katolik Darma Cendika, 2025)
This study aims to examine the effect of liquidity, solvency, and profitability on audit delay in banking sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The sample was determined using a purposive sampling method and resulted in 37 banks observed over three years, producing 111 firm-year observations. Secondary data were obtained from annual financial reports published on the IDX and analyzed using multiple linear regression. The empirical results show that liquidity has a significant effect on audit delay, indicating that a bank’s ability to meet its short-term obligations is related to the timeliness of the auditor in completing the engagement. Solvency also affects audit delay, meaning that a healthier capital structure facilitates the auditor in obtaining sufficient and appropriate audit evidence, thereby shortening audit completion time. Furthermore, profitability is found to influence audit delay; high earnings encourage management to accelerate the issuance of audited financial statements (consistent with signaling theory), while at the same time requiring auditors to exercise greater caution, making management’s document readiness a key determinant of audit duration. These findings highlight the importance of sound financial performance and early reporting preparation in order to minimize audit delay in Indonesian banking companies.